EFISIENSI TATA CARA PENGALOKASIAN, PENYALURAN, PENGGUNAAN, PEMANTAUAN DAN EVALUASI DANA DESA LIKUPANG DUA, KECAMATAN LIKUPANG TIMUR, KABUPATEN MINAHASA UTARA, PROVINSI SULUT - Armedi, Sayni; Sabijono, Harijanto; Wokas, Heince R. N. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
This study aims to determine the Efficiency of Procedure of Appropriation, Distribution, Use, Monitoring, and Evaluation of Likupang Dua Village Fund, Kec. Likupang Timur, Kab. North Minahasa, Prov. North Sulawesi if compared with Minister of Finance Regulation no. 49 of 2016. The research design used is descriptive qualitative research. The research informants were the village head, the village secretary, the village administration and the village community of Likupang Dua. The research instrument is self-study assisted by interview guides, recording devices, and observation guidelines. Data collection techniques used were interviews, observation and documentation. Technique examination of data validity using source triangulation technique. The results showed that the implementation of the policy of finance minister no. 49 years 2016 is still not efficient. Inefficiency in the utilization of Likupang Dua village funds are: (1) The procedure of allocation of Likupang Dua Village fund has been efficient with Ministerial Regulation no. 49 of 2016. (2). The Likupang Dua Village Fund Disbursement Procedure is a mismatch due to delays in the disbursement of village funds from RKUN to RKD that is Likupang Dua village due to the delay in submitting the report of the use of fund phase II. (3) Procedures for the use of Likupang Dua Village funds have been streamlined by Minister of Finances regulation no. 40). (4) The monitoring procedures of Likupang Dua Village funds have been streamlined by Ministerial Regulation no. (5) The procedures for evaluating Likupang Dua village funds have been streamlined by Minister of Finance Regulation no. 49 of 2016.Keywords: Allocation, Distribution, Usage, Monitoring, Evaluation